Natural Killer T Cells in Cancer Immunotherapy - Nair, Shiny; Dhodapkar, Madhav V. (Frontiers in Immunology, 2017)
Natural killer T (NKT) cells are specialized CD1d restricted T cells that recognize lipid antigens. Following stimulation, NKT cells lead to downstream activation of both innate and adaptive immune cells in the tumor microenvironment. This has impelled the development of NKT cell targeted immunotherapies for treating cancer. In this review, we provide a brief overview of the stimulatory and regulatory functions of NKT cells in tumor immunity as well as highlight preclinical and clinical studies based on NKT cells. Finally, we discuss future perspectives to better harness the potential of NKT cells for cancer therapy.